Do People Believe in Refilled Water? - Effiyaldi Effiyaldi; Vivi Usmayanti; Eddy Suratno; Johni Paul Karolus Pasaribu; Herry Mulyono (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Currently, Jambi residents still believe in refilling drinking water products made by themselves and sold freely in Jambi. Still, there is no data on the factors that cause / influence residents' high confidence in these products. This research aims to identify the factors that influence residents' confidence in repeated refilling drinking water in the city of Jambi. The research results show that the factors that affect people's confidence in refilled drinking water are; aspects of fairness, experience, empathy, ability in science, trust, attention, received energy, fulfillment, reliability in managing the refilled drinking water business. This research uses an aspect analysis procedure, with 434 respondents who live in the city of Jambi. Result in this study showed that the factors that influence people's trust in refilling drinking water in Jambi are; Fairness, Experience Four, Ability to Knowledge, Faith, Attention, Acceptance, Fulfillment, and Reliability. Meanwhile, the most substantial factor dominated by forming people's trust in refilled drinking water in the city of Jambi is the Fairness Factor.